La carta de crédito irrevocable confirmada como forma de pago para la importación de vehículos bajo el incoterms cif. - Quirola Tinoco, Karen Madelayne (My University, 2021)
The negotiation of international sales contracts and bank financing have currently managed to explore new markets, helping to be more competitive and increasing the confidence of importers when doing business with China. One way to increase confidence and ensure the payment of the property is to choose a secure payment method, such as the confirmed irrevocable letter of credit that exerts pressure on compliance with the conditions of the international contract, reducing the risks of international banking transactions. This research proposes the irrevocable letter of credit confirmed as a form of payment for the importation of vehicles under the Incoterms CIF, using the descriptive-exploratory methodology with an analytical approach, with information extracted from specialized scientific journals on the subject, texts from web pages, international regulations and standards, to establish a guide that facilitates the import process, participation of the actors and requirements that are required to execute the irrevocable letter of credit and apply the CIF Incoterms, according to the transport, delivery, costs and insurance of the commodity.
La negociación de los contratos de compraventa internacional y el financiamiento bancario han logrado en la actualidad explorar nuevos mercados, ayudando a ser más competitivos e incrementando la confianza de los importadores a la hora de hacer negocios con China. Una forma de aumentar la confianza y asegurar el pago del bien es escoger una forma de pago segura, como la carta de crédito irrevocable confirmada que ejerce presión en el cumplimiento de las condiciones del contrato internacional disminuyendo los riesgos de las transacciones bancarias internacionales. La presente investigación plantea la carta de crédito irrevocable confirmada como forma de pago para la importación de vehículos bajo el Incoterms CIF, utilizando la metodología descriptiva- exploratoria con enfoque analítico, con información extraída de revistas científicas especializadas en el tema, textos de páginas web, reglamentos y normas internacionales, para establecer una guía que facilite el proceso de importación, participación de los actores y requisitos que se requieren para ejecutar la carta de crédito irrevocable y aplicar el Incoterms CIF, de acuerdo al transporte, entrega, costos y seguro de la mercancía.
Keywords: IMPORTACIÓN; FORMAS DE PAGO; CARTA DE CRÉDITO; INCOTERMS